2021
DOI: 10.1186/s12889-021-11577-z
|View full text |Cite
|
Sign up to set email alerts
|

The determinant of health insurance ownership among pregnant women in Indonesia

Abstract: Background Health insurance ownership is one indicator of the readiness of pregnant women for the delivery process. The study aimed to analyze the determinants of health insurance ownership among pregnant women in Indonesia. Methods The study population was pregnant women in Indonesia. The study involved 2542 pregnant women in Indonesia. The variables analyzed included type of place of residence, age group, education level, employment status, marit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
3
25
1
Order By: Relevance
“… 24 In addition, people who are not married tend not to take advantage of health insurance services because they feel they do not need financial risk protection for their health in the future. 17 , 35 The results of other studies also show that marital status is related to NHI membership. 35 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“… 24 In addition, people who are not married tend not to take advantage of health insurance services because they feel they do not need financial risk protection for their health in the future. 17 , 35 The results of other studies also show that marital status is related to NHI membership. 35 …”
Section: Discussionmentioning
confidence: 84%
“…23 In addition, finances at old age are more stable than at a young age because they already have a relatively more regular. 17 The situation may cause a lack of NHI membership at a young age. Previous studies have also shown that age is associated with NHI membership.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study in Taiwan informed that Universal Health Coverage could minimize psychiatric services inequality in urban and rural areas [ 23 ]. Moreover, in Indonesia, NHI positively affects service utilization in all health care facilities, both government and private [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…People who have health insurance cards desire to get health service facilities if they are physically sick because they have the facilities to access them. 38 , 39 In addition, individuals who have legal health insurance will get the certainty of reasonable care under their guarantees. Health care facilities that refuse will be subject to legal sanctions from the government.…”
Section: Discussionmentioning
confidence: 99%